Processo colaborativo entre escola e família para a resolução de problemas de multiplicação no ensino fundamental - Ramos, Gislene Gonçalves (2024)
This text refers to the master's dissertation, consisting of an investigative study in the professional master's degree in Science and Mathematics Teaching of the Graduate Program in Science and Mathematics Teaching (PPGECM), of the University of Passo Fundo (UPF). An educational product was proposed, entitled "Guide for solving multiplication problems in elementary school: collaborative relationship between school and family", applied to a class of 15 students in the 3rd year of elementary school. The study takes as a problem the collaboration of the families of elementary school students in the construction of knowledge for solving multiplication problems. The social relevance of the theme is justified by contemplating aspects relevant to a mathematics teaching that relates school mathematics with the mathematics of life, this being the main point that the educator, as a research agent, should incorporate into his/her pedagogical practice. The guide proposal was developed in light of the principles of the three pedagogical moments, and the recommendations of the BNCC that guide teaching that, through problem-solving, can articulate the various fields of mathematics regarding the basic notions of multiplication. The general objective of the work was to verify how the collaborative participation of the families of elementary school students makes it possible to build knowledge of multiplication operations. The guide was applied in person, following a didactic sequence with five two-hour meetings. The research had a qualitative and quantitative approach, and data collection was carried out through a questionnaire, applied in the first meeting during a parents' meeting. In this context, three stages of the process supported by the tool were defined: data preparation, coding and analysis of responses, and preparation of the report to present the results. The similarities of the categories were analyzed using Pearson's linear correlation coefficient. The Three Pedagogical Moments Methodology proved to be an effective approach to making mathematics teaching more relevant and contextualized. It promoted active student participation, stimulated critical thinking, and encouraged the development of practical skills. Educators should consider adopting this methodology as a way to improve the quality of mathematics teaching and prepare students to face real-world challenges. The results of the analysis indicate that the guide can be very useful because, through its dynamics, students gained a better understanding of problems involving multiplication, demonstrated interest, participated and got involved in math classes, taking the knowledge acquired home and thus seeking participation and interaction with the family in homework, favoring a collaborative relationship between school and family. The educational product, in the form of a guide, that accompanies this study is available as support material for basic education teachers on the program website and on the EduCapes Portal at.